2022
DOI: 10.1007/s00439-022-02511-3
|View full text |Cite
|
Sign up to set email alerts
|

CLEC16A interacts with retromer and TRIM27, and its loss impairs endosomal trafficking and neurodevelopment

Abstract: CLEC16A is a membrane-associated C-type lectin protein that functions as a E3-ubiquitin ligase. CLEC16A regulates autophagy and mitophagy, and reportedly localizes to late endosomes. GWAS studies have associated CLEC16A SNPs to various auto-immune and neurological disorders, including multiple sclerosis and Parkinson disease. Studies in mouse models imply a role for CLEC16A in neurodegeneration. We identified bi-allelic CLEC16A truncating variants in siblings from unrelated families presenting with a severe ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…However, when faced with metabolic stressors associated with diabetes, such as high levels of glucose and fatty acids, the CLEC16A-RNF41-USP8 complex becomes destabilized and can lead to the death of β-cells. Another recent study additionally confirmed the above interaction of CLEC16A with NRDP1 also known as RNF41 [123]. CLEC16A-mediated mitophagy modulation is depicted in Figure 5.…”
Section: Regulator Of Mitophagysupporting
confidence: 60%
See 1 more Smart Citation
“…However, when faced with metabolic stressors associated with diabetes, such as high levels of glucose and fatty acids, the CLEC16A-RNF41-USP8 complex becomes destabilized and can lead to the death of β-cells. Another recent study additionally confirmed the above interaction of CLEC16A with NRDP1 also known as RNF41 [123]. CLEC16A-mediated mitophagy modulation is depicted in Figure 5.…”
Section: Regulator Of Mitophagysupporting
confidence: 60%
“…A recent study reported the first bi-allelic loss-of-function (LoF) CLEC16A truncating variants in siblings from two unrelated families with a severe neurodevelopmental disorder, including microcephaly, brain atrophy, corpus callosum dysgenesis, growth retardation, and hypotonia with severe developmental delay [123]. Using zebrafish as an in vivo model, the study shows that the loss of CLEC16A disrupts both autophagy and mitophagy, already during brain development.…”
Section: Clec16a In Neurodegenerationmentioning
confidence: 99%
“…Genome editing has been used to model human tumors such as liver cancer [70], paraganglioma [71], skin melanoma [72], and epithelioid sarcoma [73]. Among neurologic diseases, amyotrophic lateral sclerosis [74], epilepsy [75][76][77][78][79] [105,106], inner ear [107][108][109][110][111], vestibular apparatus [111], otoliths [112], brain [89, [113][114][115][116][117], neural tissue [118][119][120][121][122][123][124][125][126][127] and nervous system [128][129][130], heart [131][132][133][134][135][136][137][138][139], cardiomyocytes [140][141]…”
Section: Zebrafish As a Model Object In Studies Using Genome Editingmentioning
confidence: 99%
“…Much of the work has focused on the role of specific genes in organ formation and function, including the lens [ 99 ], retina [ 100 , 101 , 102 ], optic neurons [ 103 , 104 ], ocular vessels [ 105 , 106 ], inner ear [ 107 , 108 , 109 , 110 , 111 ], vestibular apparatus [ 111 ], otoliths [ 112 ], brain [ 89 , 113 , 114 , 115 , 116 , 117 ], neural tissue [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ] and nervous system [ 128 , 129 , 130 ], heart [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ], cardiomyocytes [ 140 , 141 , 142 , 143 ], including cardiovascular rate control [ 144 , 145 ], blood vessels [ 146 , 147 ,…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%